Initial attendance and retention in adult healthcare as criteria for transition success among organ transplant recipients. (7th April 2022) - Rea, Kelly E.; Cushman, Grace K.; Quast, Lauren F.; George, Roshan P.; Basu, Arpita; Ford, Ryan; Book, Wendy; Blount, Ronald L.
Abstract: Background: Adolescent and young adult (AYA) solid organ transplant recipients experience worsening medical outcomes during transition to adult healthcare. Current understanding and definitions of transition success emphasize first initiation of appointment attendance in adult healthcare; however, declines in attendance over time after transfer remain possible, particularly as AYAs are further removed from their pediatric provider and assume greater independence in their care. Methods: The current study assessed health‐care utilization, medical outcomes, and transition success among 49 AYA heart, kidney, or liver recipients recently transferred to adult healthcare. Differences in outcomes were examined along two transition success criteria: (1) initial engagement in adult healthcare within 6 or 12 months of last pediatric appointment and (2) retention in adult healthcare over 3 years following last pediatric appointment. Growth curve modeling examined change in attendance over time. Results: Successful retention in adult healthcare was significantly related to more improved clinical outcomes, including decreased number and duration of hospitalizations and greater medication adherence, as compared to initial engagement . Significant declines in appointment attendance over 3 years were noted, and individual differences in declines were not accounted for by age at transfer or time since transplant. Conclusions: Findings underscore support for AYAs after transfer, as significant declines in attendance were noted after initiating adult care. Clinical care teams should examine transition success longitudinally to address changes in health‐care utilization and medical outcomes. Attention to interventions and administrative support aimed at maintaining or increasing attendance and identifying risk factors and intervention for unsuccessful transition is warranted.